Effects of marine noise pollution on Mediterranean fishes and invertebrates: A review. (October 2020) - Di Franco, E.; Pierson, P.; Di Iorio, L.; Calò, A.; Cottalorda, J.M.; Derijard, B.; Di Franco, A.; Galvé, A.; Guibbolini, M.; Lebrun, J.; Micheli, F.; Priouzeau, F.; et al.
Abstract: Marine noise pollution (MNP) can cause a multitude of impacts on many organisms, but information is often scattered and general outcomes difficult to assess. We have reviewed the literature on MNP impacts on Mediterranean fish and invertebrates. Both chronic and acute MNP produced by various human activities - e.g. maritime traffic, pile driving, air guns - were found to cause detectable effects on intra-specific communication, vital processes, physiology, behavioral patterns, health status and survival. These effects on individuals can extend to inducing population- and ecosystem-wide alterations, especially when MNP impacts functionally important species, such as keystone predators and habitat forming species. Curbing the threats of MNP in the Mediterranean Sea is a challenging task, but a variety of measures could be adopted to mitigate MNP impacts. Successful measures will require more accurate information on impacts and that effective management of MNP really becomes a priority in the policy makers' agenda. Highlights: Marine noise is a widespread source of pollution in the Mediterranean Sea. Noise pollution produces a multitude of impacts on marine fish and invertebrates. Marine noise pollution affects from individuals to ecosystems. We identify knowledge gaps and potential avenues for future research. A variety of measures could be adopted to mitigate marine noise pollution.